The Application of External Ureteral Catheters in Children With Acute Kidney Injury Caused by Ceftriaxone-Induced Urolithiasis - Lin, Houwei; Geng, Hongquan; Xu, Guofeng; Fang, Xiaoliang; He, Lei; Xu, Maosheng (Frontiers in Pediatrics, 2020)
Objective: To evaluate our use of external ureteral catheters in children with acute kidney injury (AKI) resulting from ceftriaxone-induced urolithiasis. Methods: From July 2010 to June 2015, a series of 15 children, including 12 males and 3 females, were referred to our department. All of them were diagnosed of post-renal AKI and underwent emergent hospitalization. Evaluation of serum electrolytes, creatinine (Cr), blood urea nitrogen (BUN), complete blood count and blood gas analysis were completed in each child both before they were admitted, and again after surgery. Bilateral externalized ureteral catheters were placed cystoscopically in each of these patients. The composition of collected calculi was analyzed by infrared spectrography. Results: Bilateral externalized ureteral catheters were placed successfully in all patients. There were no procedure-related complications. Two days after catheter placement, the levels of serum Cr and BUN had improved in all patients, and these levels were noted to be significantly lower than before catheterization (P<0.001). Infrared spectrography demonstrated that the primary composition of all calculi collected was ceftriaxone. No recurrent AKI or renal deterioration was detected during the follow-up which ranged from 3 to 8 years. Conclusion: These results show that short-term external ureteral catheters can be effectively utilized in children with AKI caused by ceftriaxone-induced urolithiasis. We recommend this procedure as a viable replacement to indwelling stents in patients with bilateral ureteral stones.